European migration in the late twentieth century historical patterns, actual trends, and social implications - Fassmann, Heinz; Münz, Rainer 1954- (E. Elgar, 1994)
Migration in Europe is a pressing social and political issue for the policy makers of the 1990s. Drawing upon a wide body of knowledge, expertise and analysis, this book combines survey material with a series of detailed country studies on the subject over the period 1954-94.